2016
DOI: 10.3892/ol.2016.4816
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-137, hsa-miR-520e and hsa-miR-590-3p perform crucial roles in Lynch syndrome

Abstract: Abstract. The aim of the present study was to identify the differentially expressed microRNAs (DEMs) between Lynch syndrome (LS) and the normal colonic (N-C) control samples, predict the target genes (TGs) and analyze the potential functions of the DEMs and TGs. The miRNA expression dataset GSE30454, which included data of 13 LS and 20 N-C tissue samples, was downloaded from the Gene Expression Omnibus. The classical t-test in Linear Models for Microarray Data package was used for DEM identification. TG predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Our data suggested miR-137 controlled MSH2 expression via the 3′UTR, and its dysregulation putatively promoted tumorigenesis in colon cells. Recently, Zhou et al reported the role of miR-137 in LS tumor pathogenesis [ 33 ], potentially reinforcing our hypothesis that MSH2 is targeted by miR-137.…”
Section: Discussionsupporting
confidence: 87%
“…Our data suggested miR-137 controlled MSH2 expression via the 3′UTR, and its dysregulation putatively promoted tumorigenesis in colon cells. Recently, Zhou et al reported the role of miR-137 in LS tumor pathogenesis [ 33 ], potentially reinforcing our hypothesis that MSH2 is targeted by miR-137.…”
Section: Discussionsupporting
confidence: 87%
“…Balaguer et al have shown that miRs can be used in tumor classification and discrimination of sporadic and hereditary tumors with microsatellite instability (14), thus highlighting the potential role of miRs as LS biomarkers. In support, Valeri et al, Liccardo et al and Zhou et al postulated that miRs could have functional roles in LS carcinogenesis, e.g., by targeting MMR-proteins (15,16) and various tumor-suppressor genes (17). However, these studies along with other reports have assessed miR functions in the colorectum and colorectal cancer tissues and cells as well as with microarray data in silico (14)(15)(16)(17)(18)(19) but not in circulation.…”
Section: Introductionmentioning
confidence: 94%
“…Hsa-miR-590-3p is one of the mature members of the human microRNA-590 family. It has been reported that miR-590-3p is related to the development of several kinds of cancer, including colorectal cancer (CRC), 6 Lynch syndrome (a common hereditary form of CRC), 7 glioblastoma 8 and nephroblastoma. 9 However, the effect of miR-590-3p in PC cells has not been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%